Determinan Mahasiswa Dalam Memilih Peminatan Akuntansi dan Keuangan Syariah (Studi Kasus pada Mahasiswa JAFEB UB) - JULIA RAHMA KUSUMA DEWANTI (Jurnal Ilmiah Mahasiswa FEB, 2017)
The current Islamic economic system in Indonesia has shown an encouraging trend. Industrial developments, regulations and scholarship in the field of sharia would be a potential for individuals - individuals who are competent in the field of sharia. If connected with JAFEB UB, then the development in the field of sharia will be the main attraction for accounting students to choose the accounting and Islamic financeinterests. However, since the beginning of the division of interest in JAFEB UB in 2010, the number of students in Islamic accounting and finance in the least when compared with other students of interest. The purpose of this study is to examine determinants of JAFEB UB’s students intention of syaria financial and accounting in order to choose syaria financial and accounting. This study using the modified model of Theory Reasoned Action (TRA) and adding another construct, named spiritual motivation. This study using a quantitive method with stratified random sampling data collection method. This research uses survey method to JAFEB UB student of 2015, 2016 and 2017. With a sample size of 120 people. Respondents in this study are JAFEB UB students who will choose the accounting and sharia finance. Analysis of this study used SmartPLSSoftware. The results of this study indicate that the variables of spiritual motivation, intention, subjective norms and attitudes have a positive effect on intention. So if all of the above factors are positive to Islamic accounting and finance, it will generate strong intention to choose the accounting and sharia finance interests, and vice versa, if those factors are negative, it will weaken their intention to choose the accounting and finance of sharia . Keywords: Theory of Reasoned Action (TRA), attitude, subjective norm, motivation spiritual, intention.